MODERN MARKET OF INFLUENZA VACCINE PRODUCTION - Deryabina , N.D.; Gritsenko , D.A.; Aubakirova , K.P.; Baizhumanova , S.S.; Galiakparov , N.N. (Eurasian Journal of Applied Biotechnology, 2018)
Influenza virus is a negative stranded RNA virus that causes seasonal flu infections and is the reason for several epidemics that have occurred in the previous century. The high mutagenicity of the virus is mediated by error-prone RNA polymerase, which incorporates mutations into the viral genome during every replication cycle. Mutations lead to the emergence of new virus clades within subgroups, which leads to the periodic reevaluation of seasonal and pandemic vaccine contents. Vaccines usually prevent severe symptoms of flu infection only if a patient is vaccinated and infected with the same influenza subtype. Hence, there is the constant possibility of the emergence of new influenza pandemic virus. This could be prevented by either increasing the scope of vaccine efficiency or by developing methods of rapid vaccine production against any emerging subtype or clade. This article reviews vaccines against influenza virus subtypes, and modern and prospective alternative ways to increase vaccine range, breadth, and efficiency in both healthy adults and people in risk groups.